Industrial digitalization. A systematic literature review and research agenda. Issue 1 (February 2023) - Matt, Dominik T.; Pedrini, Giulio; Bonfanti, Angelo; Orzes, Guido
Abstract: This paper addresses the recent growth in publications on the topic of digitalization by systematically reviewing the literature dealing with this major technological and organizational transformation in the manufacturing sector. Our aim is to enhance the understanding of this phenomenon and provide a critical account of the state of the art of the research on industrial digitalization. After summarizing the different conceptualizations of digitalization and the stages of its evolution, we identify four thematic areas (technologies, impacts, enabling factors, and barriers) and create a meaningful segmentation of the existing publications along these dimensions. We then develop a future research agenda on industrial digitalization at both a conceptual and an empirical level, encompassing the following themes: (i) the need for a more nuanced conceptualization; (ii) the potential evolution of one or more digital technologies toward the category of "general-purpose technology"; (iii) the search for new contingency approaches; (iv) the development of accurate models of inter-firm collaboration among digital manufacturers; and (v) the elaboration of suitable solutions able to guarantee the compatibility of industrial digitalization with ethical and sustainability principles.